2013
DOI: 10.17656/jzs.10251
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic Analysis of Azmir-Goizha anticline by Nannofossils

Abstract: The Azmir-Goizha anticline elongates directly to north and northeast boundary of Sulaimani city, Kurdistan Region, NE-Iraq. The anticline is originally consisted of two main connected anticlines (Goizha and Azmir anticlines) at southwest and northwest respectively with many other smaller ones. The anticline has the length, width and elevation of about 10, 4 and 1.6 kms (amsl) respectively. It elongates from Weladar village, from southeast to Khamza village at the northwest. The anticline is relatively complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The present study does not agree with above timing of the Foreland basin since it had developed after deposition of Kometan Formation (during Campanian-Maastrichtian) ( Figure 15). This timing aided by many paleontological and sedimentological evidences such 500 m boulder and gravel conglomerate with red clastics that deposited during Maastrichtian and studied by Karim (2004), Karim, and Surdashy (2005) and Karim et al (2013).…”
Section: Problem Of the Association Of The Pseudo-bedding Thalassinomentioning
confidence: 96%
See 2 more Smart Citations
“…The present study does not agree with above timing of the Foreland basin since it had developed after deposition of Kometan Formation (during Campanian-Maastrichtian) ( Figure 15). This timing aided by many paleontological and sedimentological evidences such 500 m boulder and gravel conglomerate with red clastics that deposited during Maastrichtian and studied by Karim (2004), Karim, and Surdashy (2005) and Karim et al (2013).…”
Section: Problem Of the Association Of The Pseudo-bedding Thalassinomentioning
confidence: 96%
“…Paleontologically, Khafaf, (2014), Karim et al (2013) and Karim et al (2016) concluded that both Dokan and Gulneri Formation are occurring in all area of northeastern Iraq and there is no unconformity in the sequence of Upper Cretaceous (Figure 14, 15 and 16). Baziany (2014) found the radiolarian of Cenomanian inside Qulqula Radiolarian Formation at Chwarta area, which mentioned continuous deposition of radiolarites (very deep facies) up to middle Cenomanian.…”
Section: Problem Of the Association Of The Pseudo-mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter study concluded that the formation consist of marl and marly limestone without black shale. Karim et al (2013) found both formations on the Azmir and Goizha anticlines and prepared a detail map of the area to the north and east of Sulaimani city which show the outcrops of the two formations.…”
Section: Stratigraphy Of the Study Areamentioning
confidence: 99%
“…Recently many articles are published that are differentiated the Sarmord Formation from the Balambo Formation on the Azmir and Goizha anticlines directly at the southeast of the Qaywan anticline (Fig. 1), these articles are Karim et al (2013), Karim and Ahmad (2014), Karim and Khanaqa (2016) and Karim et al)2020). The present study focuses on the age, stratigraphy, field mapping and lithology of the formation in the Qaywan valley that is not studied before (Figs.…”
Section: Introductionmentioning
confidence: 97%